The Influence of Work Discipline, Work Environment, and Workload on Employee Performance - Mahendra Saputra, I Made Dena Julio; Diputra, Kadek Bagus Candra (PT ARRUS Intelektual Indonesia, 2025)
This study aims to analyze the influence of work discipline, work environment, and workload on employee performance at Villa Seminyak. The sample used in this study comprises all 50 employees. The data analysis method employed is multiple linear regression, along with validity and reliability testing to ensure the accuracy of the research instruments. The results indicate that work discipline has a significant positive effect on employee performance, with a coefficient value of 0.153, while the work environment has a negative but insignificant impact, with a coefficient value of -0.022. Workload also shows a significant positive effect on employee performance, with a coefficient value of 0.448. The coefficient of determination analysis reveals that 98.8% of employee performance is influenced by these three independent variables, while 1.2% is affected by other unexamined factors. Based on these findings, it is recommended that management enhance work discipline and effectively manage workload to improve employee performance at Villa Seminyak